Association between perceived stress and MAFLD partially mediated by smoking and drinking - Gong, Yan; Wang, Shengshu; Jiang, Jianan; Zeng, Qiang; Wang, Weimin; Zheng, Yansong; Lv, Wenping (Frontiers in Medicine, 2025)
BackgroundAlthough the association between stress and NAFLD has been suggested, the effect of perceived stress on MAFLD has yet to be investigated. In this study, we explore the association between perceived stress and MAFLD.MethodsWe performed a cross-sectional study including 36,847 subjects who underwent health check-ups from January 2011 to December 2021. MAFLD was defined as both fatty liver disease and metabolic dysfunction. The level of perceived stress was measured using the Chinese version of the 14-item Perceived Stress Scale (PSS-14). Logistic regression were performed to explore the association between perceived stress and MAFLD, and mediation analysis were used to examine smoking or drinking that may mediate the effects of perceived stress on MAFLD.ResultsThe prevalence of MAFLD was 37.10% (13,672/36,847). After controlling for sex, age, and BMI, the MAFLD incidence in subjects with a high level of perceived stress was significantly greater than that in subjects with a low level of perceived stress (40.4% vs. 34.9%) (P < 0.001). Perceived stress was positively associated with MAFLD [OR 1.076, 95% CI (1.005–1.153), P = 0.036]. MAFLD subjects with high perceived stress level exhibited higher rates of smoking, drinking and physical inactivity compared with non-MAFLD subjects. The mediation analysis revealed that the association between perceived stress and MAFLD was partially mediated by smoking and drinking, with a synergistic effect observed in individuals engaging in both behaviors.ConclusionsThis study provided evidence for the potential association between perceived stress and MAFLD and the mediation analysis suggested the association of perceived stress and MAFLD was partially mediated by smoking and drinking. Public health strategies should target both smoking and drinking especially in high-stress populations, given their compounded risk for MAFLD.